DEVELOPMENT OF PATIENT-CENTRED HEALTH CARE APPROACH IN THE NURSES’ AND DOCTOR ASSISSTANTS’ EDUCATION - Jankovska, Livija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Nowadays the development of health care system focuses on high quality, effective and safe health services which satisfy patients and clients’ needs. Pacient-centred health care approach and strategies are important factors to improve medical care process and results. Nurses and doctor assistants’ education practises should be based on personalised health care approach and principles. The aim of the article is to identify pacient-centred health care components and ways, how to implement them in nurses and doctor’s assisstants education in order to improve knowledge, skills, competences and attitudes for future work in multi-disciplinary team and multi-cultural environment. The study is based on theoretical and methodological analyses of the concepts and education documents. The results: the deeper understanding of the pacient-centred approach and principles, more detailed complex of skills, competences and attitudes appropriate to urgent health care problems and more competent medical worker in the individualized health care system.